Menganalisis Perkembangan Etika Manajemen Perusahaan Penelitian: Studi Bibliometrik Cooperate Social Responsibility (CSR) dan Good Corporate Governance (GCG) - Setiawati, Erma; Conteh, Abdul; Apsta, Widya; Sholahuddin, Muhammad (STIE Atma Bhakti, 2024)
Although interest in corporate management ethics is increasing, comprehensive studies on this subject are still limited. This research aims to explore research trends in corporate management ethics in Islam published in leading journals. Using a qualitative analysis approach, bibliometric analysis was carried out to examine a dataset consisting of 460 research publications indexed in Scopus between 2018 and 2022. The analysis involved the use of the R bibliometric tool and the VOS viewer application to process and analyze the data. The findings reveal a significant increase in the number of publications focusing on corporate management ethics. Journal articles are emerging as a key document type for examining corporate social responsibility (CSR) and corporate governance (CG) in the context of corporate management ethics. Among the authors, Blanco-Gonzalez and Miotto were identified as the most prolific contributors based on the number of documents written. The keywords most frequently used in this publication include corporate management ethics, corporate social responsibility (CRS), bibliometric analysis, corporate governance (CG). This research provides valuable information and insights covering various key aspects of corporate management ethics research.